Pengaruh Risiko Pembiayaan dan Inflasi terhadap Profitabilitas : Studi Kasus Bank Umum Syariah di Indonesia - Bagaskara, Doni Yusuf; Rohmadi, Rohmadi (Universitas Serambi Mekkah, 2024)
Increasing the profitability of a Sharia Commercial Bank in Indonesia cannot be separated from efforts to mitigate conditions internally and externally. This study aims to see the effect of financing risk and inflation on profitability in shari'ah commercial banks in Indonesia. This research uses secondary data in the form of financial statements of Islamic commercial banks accessed from the OJK (financial services authority) and data from the Central Statistics Agency (BPS) during the 2019-2023 period. This study used quantitative methods with the JASP 2024 software test tool and used multiple regression analysis of panel data. Researchers found that the risk of Mudharabah financing has a negative and significant influence on profitability. Meanwhile, the risk of Murabahah financing and inflation has a positive and significant influence on profitability. The implications of the study illustrate the condition of shari'ah commercial banks in overcoming internal and external conditions to increase profits.